Observer-based Predictive Repetitive Control with Experimental Validation. Issue 1 (July 2017) - Wang, Liuping; Freeman, Chris; Rogers, Eric
Abstract: This paper develops a new method for the design of predictive repetitive control systems to track periodic reference signals or reject disturbances with bandlimited frequency content. In this new design, any input disturbances present are estimated using an observer. This approach is complementary to the predictive repetitive control system designs previously reported where the periodic disturbance model was embedded in the controller. Supporting experimental results from application of the new design to a two joint robotic arm are given.